Development of electronic modules (e-modules) for islamic religious education (PAI) learning based on flipbook at SMPN 1 Tanggetada - Rahmadani, Desri; Asra, Muhammad; Nurhayati, Nurhayati (ARKA INSTITUTE, 2025)
This research aims to develop a learning media in the form of a Flipbook-based E-Module for Islamic Religious Education (PAI) for seventh-grade junior high school students and to test its validity, practicality, and effectiveness. The method used is research and development with the ADDIE model. Validation was conducted by media experts and subject matter experts, while the practicality test was carried out by PAI teachers, and the effectiveness test was conducted on students through a questionnaire. The results of the media expert validation showed that the E-Module was classified as very valid with an average score of 3.9, while the subject matter expert validation obtained an average score of 3.3, which falls into the valid category. The practicality test by teachers obtained an average score of 95, which means it is very practical, indicating that the product is easy to use and meets the learning needs. Meanwhile, the effectiveness test obtained an average score of 91, which is categorized as very effective, with the material aspect receiving the highest score of 94. Based on these results, it can be concluded that the Flipbook-based E-Module developed is suitable for use in Islamic Religious Education and can enhance student engagement and understanding. This product can also serve as an alternative innovative learning media in the digital era.